Revisiting the Role of Augmentative and Alternative Communication in Aphasia Rehabilitation - Dietz, Aimee; Wallace, Sarah E.; Weissling, Kristy (American Journal of Speech-Language Pathology, 2020)
Purpose The purpose of this article is to revisit the role of augmentative and alternative communication (AAC) in poststroke aphasia rehabilitation. The authors' intent is to provide a viewpoint that expands the use of AAC in poststroke aphasia rehabilitation. Specifically, we seek to clarify the role of AAC in restorative and participation approaches to aphasia rehabilitation while also considering the role of AAC in a comprehensive treatment plan. The authors support their viewpoint with citations from both the historic and contemporary literature on aphasia rehabilitation. Conclusions A thought-provoking viewpoint on the role of AAC in poststroke aphasia rehabilitation is proposed. More specifically, the versatility of AAC strategies is reviewed, with an emphasis on how AAC can be used to empower people with aphasia to fully participate and engage in life activities with increased independence. Moreover, we argue that AAC can be viewed as a dual-purpose tool that can simultaneously serve to drive intersystemic reorganization resulting in some improved language performance-and perhaps restoration of language function-while offering a communication alternative during inevitable anomic events.
Keywords: Aphasia; Communication; Communication Aids for Disabled; Humans; Language